Prostate-Specific Antigen as a Marker of Hyperandrogenism in Women and Its Implications for Antidoping. (6th January 2020) - Musrap, Natasha; Diamandis, Eleftherios P
Abstract: BACKGROUND: Since its discovery in the 1970s, prostate-specific antigen (PSA) has become widely known as a biomarker of prostate cancer in males but has often been overlooked in female malignancies. Although the serum concentration of PSA differs between men and women by about 1000-fold, studies have suggested that PSA concentrations drastically differ among healthy females and those who exhibit increased androgen production. CONTENT: There have been reports of increased PSA expression in women exhibiting hyperandrogenic states, including polycystic ovary syndrome and hirsutism, as well as marked increases in a subset of breast cancer patients. These findings have not only revealed the remarkable diagnostic potential of PSA in a diverse range of clinical conditions but also point to its potential of becoming a useful biomarker of steroid hormone doping among female athletes. Recently, highly sensitive assays that can measure PSA at low limits of detection have been developed, which will aid in the discrimination of PSA between these different conditions. SUMMARY: The overall aim of this review is to revisit the expression of PSA in hormonally-regulated tissues and in female malignancies, and to demonstrate how the regulation of PSA permits its use in antidoping initiatives.